FREQUENCY AND STRUCTURE OF BENIGN SOFT TISSUE FORMATIONS IN THE MAXILLOFACIAL AREA - Tkachenko, P.I.; Rezvina, K.Yu.; Shvets, A.I.; Popelo, Yu.V. (World of Medicine and Biology, 2020)
The article considered our own observation results and retrospective analysis of archival material of the Maxillofacial Department of M.V. Sklifosovsky Poltava Regional Clinical Hospital and Surgical Department of the Poltava City Children’s Clinical Hospital from 2008 to 2018. It was found that among adults the number of patients with benign soft tissue formations of the face and neck is 4.9%, and in children – 7.8% of the total number of inpatients. Most of them were bronchiogenic cysts of the lateral part of the neck (152 – 26.3%) and atheromatous plaques (147 – 25.4%). They mostly occured at the age of 22 to 60 years, men suffered more often (205 - 35.5%). The largest number of discrepancies in the diagnosis at the prehospital phase were patients with epidermal cysts – 38 (7.9%). As for pediatric population, their number was 7.8% of the total number of inpatients. Neoplasms of dysontogenetic origin predominate, among which the most common were dermoid cysts – 92 patients (32.4%) and haemangiomas– 74 patients (26%). Less common were ranulae – 36 cases (12.7%), bronchiogenic cyst – 17 cases (6%) and atheromatous plaque – 16 cases (5.6%). They were found more often in the nursery age – from 1 to 3 years.